MENGEMBANGKAN WIRAUSAHA DI PONDOK PESANTREN - Endah Sudarsih (JURNAL SOSIAL HUMANIORA (JSH), 2010)
Socialization and development of entrepreneurship in Islamic Boarding School is vitally important. It will lighten the operational cost funding, and also improve the independence of boarding school. On the other hand, it will also train students’ independency after graduate from the boarding school. This activity is designed to supply students in Pondok Pesantren At-Taufiq with a skill and effort in founding a business unit. The skill that is interested is computer, while the founded business is computer service. In Kecamatan Diwek and its surroundings, it is very rare to be found. The form of this vucer-activity is an entrepreneurship training program: service computer and computer network installation, and also making a business proposal. As continuation of training, it is delivered a set of computer as capital of forming a computer service business unit in Pondok Pesantren At-Taufiq. There are some constraints in execution of this program activity, such as human resources (SDM) in Pondok Pesantren that is lack of time and ability in permeating the knowledge. So that it is required more computer training for several times before computer service business unit could be actually realized and fulfill the activity purpose.